Legal Force Of The Binding Agreement For Sale And Purchase In Full And The Power To Sell With A Non-Electronic Id Card Identity - Raharjo, Prasetyo; Pujiyono, Pujiyono; Suryono, Arief (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
A Sale and Purchase Binding Agreement (PPJB) is an obligatoir agreement that usually includes a power to sell clause. Under certain conditions, illegal acts may arise such as the seller disappearing after signing the deed as in the case of a civil case registered in the Karanganyar District court number 2 / Pdt.G / 2021 / PN Krg. The obligation to include an Electronic KTP in the transfer of rights raises problems with the paid PPJB and selling power made during the transition of self-identity from Non-Electronic KTP to Electronic KTP, namely in 2011 at which time the process of transferring rights at the National Land Agency (BPN) office was still received using a non-electronic KTP. This research method is juridical normative to determine the legal strength of paid off PPJB and the power to sell with a non-electronic ID card identity. The legal force of PPJB in full and the power to sell with a non-electronic ID card identity is valid and has binding legal consequences and must be implemented by the parties as ordered by law, if the PPJB is carried out and meets the requirements for the validity of the agreement as stipulated in Article 1320 of the Civil Code, the fulfillment of the principles of the agreement and the elements of the agreement therein and does not violate the provisions, decency and decency and the laws in force at the time the deed was made. Apart from that, the legal force of proof attached to an authentic deed is perfect in the sense that the proof is sufficient with the deed itself unless there is evidence of an opponent who proves otherwise and the judge is bound by the deed itself as long as the deed made is in accordance with the provisions of the validity of a deed as stipulated in the UUJN and Civil Code.